2015
DOI: 10.1177/1075547015617942
|View full text |Cite
|
Sign up to set email alerts
|

Ethics Information Seeking and Sharing Among Scientists

Abstract: As nanotechnologies permeate our daily lives, it is increasingly important that we understand the ethical considerations of these innovations and to what extent scientists attend to these considerations. Guided by the theory of reasoned action and an extended version of that model that includes prior knowledge, sense of responsibility, and ethics involvement, we surveyed a sample of nanoscientists to explore their ethics information seeking and sharing. Path analyses support the theory of reasoned action as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
(90 reference statements)
3
8
0
Order By: Relevance
“…Indeed, in their study of online information seeking and sharing, Li and colleagues (2018) found that risk and benefit perceptions were significant predictors of individual's intentions to seek and share health information via social media. These findings are consistent with similar research that found support for shared predictors of information seeking and sharing in the contexts of nanotechnology (Kahlor et al 2016) and climate change (Yang, Kahlor, and Griffin 2014). The latter study specifically suggested the applicability of Griffin, Dunwoody, and Neuwirth (1999) risk information seeking and processing model to information sharing behaviors.…”
Section: Literature Reviewsupporting
confidence: 90%
See 3 more Smart Citations
“…Indeed, in their study of online information seeking and sharing, Li and colleagues (2018) found that risk and benefit perceptions were significant predictors of individual's intentions to seek and share health information via social media. These findings are consistent with similar research that found support for shared predictors of information seeking and sharing in the contexts of nanotechnology (Kahlor et al 2016) and climate change (Yang, Kahlor, and Griffin 2014). The latter study specifically suggested the applicability of Griffin, Dunwoody, and Neuwirth (1999) risk information seeking and processing model to information sharing behaviors.…”
Section: Literature Reviewsupporting
confidence: 90%
“…As mentioned earlier, a number of information-sharing studies assert that seeking and sharing behaviors share motivational antecedents (Kahlor et al 2016;Lee and Jin 2019;Lin et al 2016;Myrick 2017;Yang, Kahlor, and Griffin 2014). Among the most notable motivators of information sharing to emerge from that body of work were: information seeking (Lin et al 2016;Yang, Kahlor, and Griffin 2014); informational subjective norms (Kahlor et al 2016;Yang, Kahlor, and Griffin 2014), attitude toward sharing (akin to RISP's relevant channel beliefs; Kahlor et al 2016;Lin et al 2016), negative affect (Yang, Kahlor, and Griffin 2014), and prior knowledge and insufficiency (Yang, Kahlor, and Griffin 2014).…”
Section: Risp and Information Sharingmentioning
confidence: 90%
See 2 more Smart Citations
“…These were shared electronically before a face-to-face meeting that began several cycles of synthesis and analysis, conducted both synchronously and asynchronously, in which proposed competencies were grouped, emerging themes were and their work. For many researchers, while reflection on the ethical conduct of their research is the norm, reflection on the societal-level implications of their work is rare (Kahlor, Dudo, Liang, Lazard & AbiGhannam, 2016). The vision for the competencies, therefore, is not that they are a set of points to make at a workshop, but rather they are a framework to inform the goal-driven design of a research communications curriculum.…”
Section: Ethics Competencies For Research Communicationmentioning
confidence: 99%